1972
DOI: 10.1002/neu.480030205
|View full text |Cite
|
Sign up to set email alerts
|

Preparative resolution and identification of synaptic components of rat neocortex

Abstract: SUMMARYA varity of density gradient centrifugation techniques have been used with varying degrees of success, for the preparative resolution of pinched off nerve endings, i.e. "synaptosomes," and synaptic components from brain homogenates. The physics of such gradients was critically considered from the standpoint of improving the degree of resolution of particulate classes and preserving morphological integrity. A procedure, using continuous linear Ficoll gradients, is presented which yields improved particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

1973
1973
1983
1983

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Structures morphologically similar to the curved, dark-staining profiles seen in the preparation of Garey et al (1972) have also been found in our synaptosome fractions. Elias (1971) has shown that dumbbell profiles in thin sections are most consistent with a cup shape in three dimensions, that is, "a torus with a membrane closing the hole."…”
supporting
confidence: 79%
See 3 more Smart Citations
“…Structures morphologically similar to the curved, dark-staining profiles seen in the preparation of Garey et al (1972) have also been found in our synaptosome fractions. Elias (1971) has shown that dumbbell profiles in thin sections are most consistent with a cup shape in three dimensions, that is, "a torus with a membrane closing the hole."…”
supporting
confidence: 79%
“…Finally D shows a profile of a free structure similar to that labeled "free postsynaptic membrane" by Garey et al (1972). Figure 2 shows a structure which has a dumbbell-shaped profile in the thin section, also ex- Figure 1 shows a field from the P,B, pellet.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Aggregation of vesicles is also produced by ischemia (Williams and Grossman, 1970) and by experimental allergic encephalomyelitis (Ross and Bornstein, 1969), as well as by toxins (triorthocresylphosphate and methionine sulfoximine -De Robertis et al, 1967b) and certain neuropathies (Alzheimer's disease - Gonatas et al, 1967).…”
Section: Discussionmentioning
confidence: 98%